2012
DOI: 10.1186/1471-2350-13-5
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide association study of pulmonary tuberculosis susceptibility in Indonesians

Abstract: BackgroundThere is reason to expect strong genetic influences on the risk of developing active pulmonary tuberculosis (TB) among latently infected individuals. Many of the genome wide linkage and association studies (GWAS) to date have been conducted on African populations. In order to identify additional targets in genetically dissimilar populations, and to enhance our understanding of this disease, we performed a multi-stage GWAS in a Southeast Asian cohort from Indonesia.MethodsIn stage 1, we used the Affym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 39 publications
1
62
2
Order By: Relevance
“…Genetic variability is an important determinant of the effectiveness of the host immune response to M. tuberculosis [3]. Several lines of evidence, including twin studies [4], genome-wide linkage studies [5], and genome-wide association studies [6,7], have demonstrated that host genetic factors play a critical role in effecting the infected individuals eventually to develop TB.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variability is an important determinant of the effectiveness of the host immune response to M. tuberculosis [3]. Several lines of evidence, including twin studies [4], genome-wide linkage studies [5], and genome-wide association studies [6,7], have demonstrated that host genetic factors play a critical role in effecting the infected individuals eventually to develop TB.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the host genetic susceptibility to TB encompass twin (3,4), linkage, candidate gene association, and genomewide association studies (5)(6)(7)(8)(9)(10)(11)(12). We and others have identified associations between common polymorphisms in innate immunity genes and susceptibility to TB and clinical phenotypes (6,8,11,13).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Host genetic factors explain, at least in part, why some people are more or less susceptible to infection. Several lines of evidence, including twin studies (48,148,242), genome-wide linkage studies (21,49,136,144,148,217), and recently published genome-wide association studies (GWAS) (135,172,229), demonstrate that host genetics strongly influences susceptibility to TB. However, assessing the contributions and functional consequences of specific genetic variations (polymorphisms) in the human genome to host susceptibility or resistance to TB remains a longstanding challenge of population genetics research, with many questions unanswered.…”
mentioning
confidence: 99%